Syringofibroadenoma: Benign eccrine sweat gland tumor - A rare case report - Banyameen Iqbal; Prachi Khandekar; Indranil Dey; Harsh Kumar (Wolters Kluwer Medknow Publications, 2019)
Eccrine syringofibroadenoma (ESFA) is a rare adnexal tumor. It was first described by Mascaro in 1963. They are predominantly seen on the extremities of middle aged to elderly patients. Clinically, ESFA is classified into five subtypes. Solitary ESFA, the most common subtype, usually presents as a skin-colored papule, plaque, or nodule. The histomorphological and immunohistochemical features are necessary for their diagnosis and are also required to differentiate them from their malignant counterpart, eccrine syringofibrocarcinoma.